PENERAPAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) PADA SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PENERIMAAN CALON ANAK BUAH KAPAL (STUDI KASUS PT. TIMAS SUPLINDO) - Daffa Satria Maulana; Munawaroh Munawaroh (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
The selection The selection process for prospective crew members is a crucial stage for the company, especially at PT. Timas Suplindo. However, it is often difficult to determine prospective crew members who are competent in their fields. The selection process for prospective crew members is considered ineffective because decision making still has to consider many aspects. The purpose of this study is to create a website-based application and make it easier for the company, especially Human Resource Development (HRD), to obtain competent crew members who meet the specified criteria. This method was chosen because the assessment process is transparent because each stage of assessment and weighting can be tracked and increases accountability in decision making. .